Analyzing Grammatical Errors in Describing Graphs Among EFL Students - Dini Riandini (Pustaka Digital Indonesia, 2025)
In the process of learning English, learners often commit common errors in applying correct grammar. One frequent issue is the occurrence of grammatical errors when describing graphs in English. This skill is particularly important, especially for EFL students, as it is applicable in various academic and professional contexts. Therefore, the present study aims to identify the types of grammatical errors commonly made by learners in this context. Employing a descriptive qualitative approach, this research analyzed 30 samples of students’ written work in which they described a chart in English. The data were categorized using Dulay’s Surface Strategy Taxonomy, which classifies errors into four types: addition, omission, misformation, and misordering. The findings reveal that omission was the most frequent type of error, accounting for 34.78% of the total, followed by addition at 31.88%, while misordering was the least frequent, occurring in 10.14% of cases. It is recommended that students receive adequate instruction in basic grammar to improve their accuracy when describing graphs in English, thereby reducing such errors. Furthermore, the study is expected to provide valuable insights for lecturers in designing a General English syllabus that places greater emphasis on strengthening students’ foundational grammar skills.